Distinct and complementary roles of CD4 T cells in protective immunity to influenza virus - Sant, Andrea J. (Curr Opin Immunol, 2018)
CD4 T cells play a multiplicity of roles in protective immunity to influenza. Included in these functions are help for high affinity antibody production, enhancement of CD8 T cell expansion, function and memory, acceleration of the early innate response to infection and direct cytotoxicity. The influenza-specific CD4 T cell repertoire in humans established through exposures to infection and vaccination has been found to be highly variable in abundance, specificity and functionality. Deficits in particular subsets of CD4 T cells recruited into the response result in diminished antibody responses and protection from infection. Therefore, improved strategies for vaccination should include better methods to identify deficiencies in the circulating CD4 T cell repertoire, and vaccine constructs that increase the representation of CD4 T cells of the correct specificity and functionality.